Liver and systemic hemodynamics in children with cirrhosis: Impact on the surgical management in pediatric living donor liver transplantation. Issue 11 (26th October 2017) - de Magnée, Catherine; Veyckemans, Francis; Pirotte, Thierry; Menten, Renaud; Dumitriu, Dana; Clapuyt, Philippe; Carbonez, Karlien; Barrea, Catherine; Sluysmans, Thierry; Sempoux, Christine; Leclercq, Isabelle; Zech, Francis; et al.
Abstract : Cirrhosis in adults is associated with modifications of systemic and liver hemodynamics, whereas little is known about the pediatric population. The aim of this work was to investigate whether alterations of hepatic and systemic hemodynamics were correlated with cirrhosis severity in children. The impact of hemodynamic findings on surgical management in pediatric living donor liver transplantation (LT) was evaluated. Liver and systemic hemodynamics were studied prospectively in 52 children (median age, 1 year; 33 with biliary atresia [BA]). The hemodynamics of native liver were studied preoperatively by Doppler ultrasound and intraoperatively using invasive flowmetry. Portosystemic gradient was invasively measured. Systemic hemodynamics were studied preoperatively by Doppler transthoracic echocardiography and intraoperatively by using transpulmonary thermodilution. Hemodynamic parameters were correlated with Pediatric End‐Stage Liver Disease (PELD) score and the histological degree of fibrosis (collagen proportionate area [CPA]). Cirrhosis was associated with a 60% reduction of pretransplant total liver flow (n = 46; median, 36 mL/minute/100 g of liver) compared with noncirrhotic livers (n = 6; median, 86 mL/minute/100 g; P  = 0.002). Total blood flow into the native liver was negatively correlated with PELD ( P  < 0.001) and liver CPA ( P  = 0.005). Median portosystemic gradient was 14.5 mm Hg in children with cirrhosis and positively correlated with PELD ( P  < 0.001). Portal vein (PV) hypoplasia was observed mainly in children with BA ( P  = 0.02). Systemic hemodynamics were not altered in our children with cirrhosis. Twenty‐one children met the intraoperative criteria for PV reconstruction using a portoplasty technique during the LT procedure and had a smaller PV diameter at pretransplant Doppler ultrasound (median = 3.4 mm; P  < 0.001). Cirrhosis in children appears also as a hemodynamic disease of the liver, correlated with cirrhosis severity. Surgical technique for PV reconstruction during LT was adapted accordingly. Liver Transplantation 23 1440–1450 2017 AASLD.